Association between echocardiographic features and inflammatory biomarkers with clinical outcomes in COVID-19 patients in Saudi Arabia - Abohamr, Samah I.; Abazid, Rami M.; Alhumaid, Mohammed K.; Abdulrahim, Abubaker E.; Aldossari, Mubarak A.; Khedr, Lamiaa; Werida, Rehab H.; Alkheledan, Haifa S.; Aleid, Yazeed S.; Abdelhamid, Sara W.; Al Mefarrej, Abdulmohsen; Abdelhamid, Ahmed W.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Abstract: Background: Respiratory infections are one of the most common comorbidities identified in hospitalized patients. The coronavirus disease 2019 (COVID-19) pandemic greatly impacted healthcare systems, including acute cardiac services. Aim: This study aimed to describe the echocardiographic findings of patients with COVID-19 infections and their correlations with inflammatory biomarkers, disease severity, and outcome. Methods: This observational retrospective study was conducted between June 2021 and July 2022. The analysis included all patients diagnosed with COVID-19 who had transthoracic echocardiographic (TTE) scans within 72 hours of admission. Results: The enrolled patients had a mean age of 55.6 ± 14.7 years, and 66.1% were male. Of the 490 enrolled patients, 203 (41.4%) were admitted to the intensive care unit (ICU). Pre-ICU TTE findings showed significantly higher sever right ventricular dysfunction (28 [13.8%] vs. 23 [8.0%]; P = 0.04) and left ventricular (LV) regional wall motion abnormalities (55 [27.1%] vs. 29 [10.1%]; p ˂ 0.001) in ICU compared to non-ICU patients. In-hospital mortality was 11 (2.2%), all deaths of ICU patients. The most sensitive predictors of ICU admission (p ˂ 0.05): cardiac troponin I level (area under the curve [AUC] = 0.733), followed by hs-CRP (AUC = 0.620), creatine kinase-MB (AUC = 0.617), D-dimer (AUC = 0.599), and lactate dehydrogenase (AUC = 0.567). Binary logistic regression showed that reduced LV ejection fraction (LVEF), elevated pulmonary artery systolic pressure, and dilated right ventricle were echocardiographic predictors of poor outcomes (p ˂ 0.05). Conclusion: Echocardiography is a valuable tool in assessing admitted patients with COVID-19. Lower LVEF and pulmonary hypertension and higher D-dimer, C-reactive protein, and pro B-type natriuretic peptide levels were predictors of poor outcomes.